West of redemption [videorecording (DVD)] - Becerra, Tony; Estes, Larry; Daine, Meagan; Zane, Billy; Alejandro, Kevin, 1976-; Klaveno, Mariana; Williams, T. J.; Burdette, Denise; Smith, BC (Indican Pictures, 2018)
"Late one night, a knock on the door interrupts a husband and wife's evening, changing their lives forever. When Hank (Billy Zane) and Becky (Mariana Klaveno) open the door to a traveler (Kevin Alejandro) whose truck broke down, it opens a nightmare for everyone unwinding a complicated web of mysteries that ends with a kidnapping, a dead body and a dark history."--Container